E47 regulates hematopoietic stem cell proliferation and energetics but not myeloid lineage restriction - Yang, Qi (American Society of Hematology, 2011)
The immune system is replenished by self-renewing hematopoietic stem cells (HSCs) that produce multipotent progenitors (MPPs) with little renewal capacity. E-proteins, the widely expressed basic helix-loop-helix transcription factors, contribute to HSC and MPP activity, but their specific functions remain undefined. Using quantitative in vivo and in vitro approaches, we show that E47 is dispensable for the short-term myeloid differentiation of HSCs but regulates their long-term capabilities. E47-deficient progenitors show competent myeloid production in short-term assays in vitro and in vivo. However, long-term myeloid and lymphoid differentiation is compromised because of a progressive loss of HSC self-renewal that is associated with diminished p21 expression and hyperproliferation. The activity of E47 is shown to be cell-intrinsic. Moreover, E47-deficient HSCs and MPPs have altered expression of genes associated with cellular energy metabolism, and the size of the MPP pool but not downstream lymphoid precursors in bone marrow or thymus is rescued in vivo by antioxidant. Together, these observations suggest a role for E47 in the tight control of HSC proliferation and energy metabolism, and demonstrate that E47 is not required for short-term myeloid differentiation.